Effects of tissues and geometric shapes of phantoms on the specific energy absorption rate. Issue 3 (25th January 2018) - Saleh, Gameel; Sibaii, Fatima; Alashban, Najla; Alkhateeb, Haneen; Hegazi, Fatma; Hegazi, Mariam
Abstract: In this article, the effects of tissues and geometric shape complexity of human body and head phantoms on the performance of radio frequency (RF) antennas/coils are investigated. The magnetic field, H, electric field, E, and the specific energy absorption rate ( S A R ) of a meander dipole RF coil are calculated. The coil has been designed and fabricated at the University laboratory to resonate at the operating frequency of 7 T magnetic resonance imaging machines. Three phantoms of different geometries, homogeneous and inhomogeneous, are used in this work. It was noticed that the homogeneous spherical human head phantom exhibited higher peak SAR value (by an amount of 30%) than a homogeneous simple rectangular body model. Similarly, the geometric shape complexity of the homogeneous SAM head phantom played the dominant role in the accuracy of SAR results. The coil with the homogeneous SAM head model exhibited higher peak SAR value (by an amount of 84%) than the homogeneous spherical head model. In contrary, the inhomogeneous multilayered spherical head phantom exhibited SAR value less than the single‐layered homogenous one (by 40%). The complexity of tissues, in particular, the adult skull bone thickness, reduces the intensity of power coupled to the brain.